Kadrovska reprodukcija v poklicnem izobraževanju - Kolenc, Janez (Šolsko polje, 2007)
Principle of progresiveness by introduction of dual organization is derived only by possibility, that certain branch e.g. individual companies are taking over co-responsability in vocational education in sense of personnel reproduction. We may allow no way, that should this solution understood by private sector of employers as a favour to state which carried out programmes of vocational education. This would guide dual system to classical model of apprenticeship. In this case we could not speak any more about personnel reproduction from the site of economic sphare, what is the excellency of a dual system of vocational education. The legitimacy of criticism of strategy of introduction of dual education as ingredient of system regulation of vocational education goes by also from one-sided deducing of renovated programmes on the middle stage of vocational education. Programmes of dual system of lower vocational education still didn't begin to live in practice . Strategy of development must introduce basic starting point of further preparing of new programmes. It is pointless to develop numerous of a new programmes and to file high means to their producing, if they stay still uncovered. It is more important to assure the quality of education circumstances for their execution and for the rise of the quality of educationin a whole. In this way will social capital, that affords dual systemof vocational education, compounded and reproduced competitive professions on the segmental Slovene labor market.
Keywords: izobraževalni programi; kadrovska reprodukcija; poklicne šole; poklicno izobraževanje; Slovenija